Impacto da Tecnologia na Democracia: avaliando o aumento ou alteração da participação social na elaboração de politicas públicas municipais - Sanchez, Ricardo Lopes (Universidade Federal de São Carlos, 2020)
While a part of the literature argues that the expansion of ICTs and global inclusion are fundamental to the social processes of freedom and democracy in the present millennium, another part of the literature questions whether the use of ICTs has a positive influence on the process of expanding democracy. The present research is guided by the following research question: can ICTs promote more effective social participation in the definition of municipal public policies? Therefore, the study has as general objective to know the use of ICTs through a case study in order to analyze the impact of society's participation in the formulation of municipal public policies. Through a case study with the Municipal Council of Casa Branca, city of São Paulo, the study analyzes a Public Consultation carried out with the use of ICTs on the bill that deals with the concession for 30 years of the water treatment service and sewage from the municipality. From this case study in light of theoretical studies, the research hopes to contribute to the knowledge about the use of ICTs in the formulation of municipal public policies. The study also presents a proposal of measures capable of intensifying participatory democracy through the use of ICTs, considering as many aspects of the Internet, digital communication tools as the legal and formal aspects of the application of technology.
Impact of Technology on Democracy: evaluating the increase or change in social participation in the elaboration of municipal public policies
Keywords: Participação social; TIC e democracia; Democracia participativa; e-governo; Social participation; ICT and democracy; e-government; Participatory democracy; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE DO PROCESSO DECISORIO